The Effects of Parenting Styles on Sex-Role Ideologies of Pru West Senior High Students - Adangabe, Amos Amuribadek; Gideon, Ankama Mensah; Inkoom, Daniel; Emmanuella, Dogbey Alice (South Asian Journal of Social Sciences and Humanities, 2021)
No two parents view things in the same way when it comes to raising their children. In this light, the current study attempted to establish a link between parenting methods and gender role ideas. This study used a correlational research design. We selected 300 individuals from a population of 1480 using stratified and simple random selection procedures. The participants' parenting styles were assessed using Buri's (1991) Parental Authority Questionnaire (PAQ), and their sex role beliefs were assessed using Williams and Best's Sex-Role Ideology Scale (SRIS) (1990). Moment of Pearson-Product Correlation was used to determine the relationship between parenting methods and sex role ideology, while regression was utilised to determine the variables' predictions. It was discovered that parenting techniques had no effect on the participants' sex-role ideas. Individuals with an authoritative parenting style, on the other hand, were more likely to develop a more modern sex-role ideology, whereas those with an authoritarian parenting style developed a more conventional sex-role ideology. Additionally, both sex and religion predicted modern and traditional sex-role ideas, respectively. Tribe anticipated an authoritative parenting style without regard for either permissive or authoritarian parenting methods. The study recommends that because parenting styles are related to sex-role ideology, guidance and counselling coordinators should place a premium on the most effective parenting style in order to help students develop an acceptable sex role ideology.
Keywords: Parenting Styles; Sex-Role; Ideology; Pru west